REFLETINDO SOBRE O CUIDADO ODONTOLÓGICO E A RESPONSABILIDADE PARA COM A VIDA E O VIVER MAIS SAUDÁVEL DAS PESSOAS IDOSAS - Ana Lúcia Schaefer Ferreira de Mello; Alacoque Lorenzini Erdmann (Universidade Federal do Paraná, 2003)
The article presents a reflection about some questions that are involved with oral health care provided to elderly people according to the ethic of responsability of Hans Jonas. Considering the oral health conditions of elderly people, the article discuss the dimensions of care and reflects if the knowledge and practices of oral health care are compromised with an ethics of responsibility of life and with a better and healthy living.